2002
DOI: 10.1212/wnl.58.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of somnolence in Parkinson’s disease: Comparison with age- and sex-matched controls

Abstract: The authors found a significantly higher prevalence of daytime somnolence in 201 patients with PD compared with 214 age- and sex-matched healthy control subjects (Epworth Sleepiness Scale score 5.6 vs 4.6). The prevalence of "sleep attacks" (SA) was about seven times higher in patients with PD than in control subjects (13.9% vs 1.9%; p < 0.0005). Multivariate analysis demonstrated that a higher dose of levodopa and longer duration of disease significantly predicted for SA in patients with PD. Epworth Sleepines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(120 citation statements)
references
References 10 publications
10
102
3
2
Order By: Relevance
“…The occurrence of EDS among patients with PD was lower in Asian than in Caucasian populations in the literature. Studies from Asia using the ESS have reported that the prevalence of EDS ranged from 15.1% to 32.3%; however, prevalence ranging from 40.6% to 57% was reported for Europe and North America (Brodsky et al., 2003; Chen et al., 2015; Goldman et al., 2013; Hobson et al., 2002; Louter et al., 2012; Poryazova et al., 2010; Ratti et al., 2015; Setthawatcharawanich et al., 2014; Tan et al., 2002; Yu et al., 2015; Zhu et al., 2016) (Table 3). Disease severity, disease duration, dopaminergic therapy, and hypnotic medication have been suggested to contribute to EDS; however, neither of them could fully explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of EDS among patients with PD was lower in Asian than in Caucasian populations in the literature. Studies from Asia using the ESS have reported that the prevalence of EDS ranged from 15.1% to 32.3%; however, prevalence ranging from 40.6% to 57% was reported for Europe and North America (Brodsky et al., 2003; Chen et al., 2015; Goldman et al., 2013; Hobson et al., 2002; Louter et al., 2012; Poryazova et al., 2010; Ratti et al., 2015; Setthawatcharawanich et al., 2014; Tan et al., 2002; Yu et al., 2015; Zhu et al., 2016) (Table 3). Disease severity, disease duration, dopaminergic therapy, and hypnotic medication have been suggested to contribute to EDS; however, neither of them could fully explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity, disease duration, dopaminergic therapy, and hypnotic medication have been suggested to contribute to EDS; however, neither of them could fully explain this discrepancy. The disease severity of the patients were similar in these Western and Asian studies, with H&Y stages between 2 and 3 (Poryazova et al., 2010; Setthawatcharawanich et al., 2014; Tan et al., 2002; Yu et al., 2015; Zhu et al., 2016). In a study of 638 Canadian patients with PD with H&Y stage of 2.2 ± 0.68, Hobson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four had a symptomatic RBD, 11 of which had PD [12]. In questionnaire-based studies asking for sleepwalking/nighttime wandering in PD patients, frequencies ranging from 2% (4/201) [13], 3% (2/61, resp. 2/66) [9,14] to 5% (16/303) [15] can be found in the literature, however, no detailed characteristics of the phenomenon were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated Epworth Sleep Scale (ESS) scores, male gender, long duration and severity of the disease are the major risks for EDS [22]. Several studies indicated that dopaminergic load acts as a correlative factor for a higher ESS score and increased daytime sleepiness in PD [23,24]. In addition, Yi PL et al proved that IL-1b in the hypothalamus mediates the EDS in the rotenone rat model and that the TNF-NF-jB signaling is involved in another hemiparkinsonian rat model [25,26].…”
Section: Sleep Disordersmentioning
confidence: 99%